Optimalisasi Desain Struktur Gedung Interdisciplinary Engineering (IDE) – Fakultas Teknik Universitas Indonesia dengan Memanfaatkan BIM (Building Information Modelling) - Citra Anindya Larasati; Dendi Ahmad Dzaky; Asri Nurdiana; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2024)
Project design is a step in the construction process that determines the technical requirements to be applied when the project is constructed. BIM (Building Information Modeling) is a form of technological innovation used in project design. BIM (Building Information Modeling) has become the main factor for increasing efficiency and accuracy; using BIM, everything related to design, construction, scheduling, and costs can be integrated into one digital platform that all stakeholders can access. In this paper, the structural planning optimization of the Interdisciplinary Engineering (IDE) Building - Faculty of Engineering, University of Indonesia, will be carried out. This building planning refers to (SNI-2847-2019) concerning Structural Concrete Requirements for Buildings and (SNI-1726-2019) concerning Procedures for Planning for Earthquake Resistance of Structures. Outputs are generated through superstructure and substructure plans, the design of foundation structures, columns, beams, and plates, 2D Detail Engineering Design (DED), 3D modeling, and construction management plans in the form of Budget Plans and scheduling.